The Conception of Institutional Business: Research Directions and Methods - Prosekin, Alexander K.; Shkuropatskaya, Violetta K. (International Journal of Economics and Financial Issues, 2016)
Institutional business is a component of business activity directed on the improvement of already existing and also the creation and introduction of new social and economic institutes. The creation of conditions for business, especially in the sphere of material production, is the main purpose and a component of the economic policy for any transitional economy. The paper presents an analysis of the main researches of the conception of institutional business, published in academic scientific magazines over the period from 2002 to 2015. Stages of the development of the conception were revealed during the research, the main directions of researches of institutional business, and also areas of scientific researches in which the action of theory of institutional business were not yet studied. As a result the priority directions in the research of institutional business from the point of view of scientists-researchers of this area were defined. The authors have considered data collection methods in researches of the conception of institutional business on the basis of the article case. The received conclusions will help to continue the study of institutional business from a position of concrete disciplines: macro and microeconomics, management, psychology, institutional economy, business and others. Keywords: institutional business, institutional theory, business, institutes, institutional economy JEL Classifications: M21, M49, N8